Cytokine expression in serum and cerebrospinal fluid in non-inflammatory polyneuropathies. Issue 11 (11th June 2008) - Ludwig, J; Binder, A; Steinmann, J; Wasner, G; Baron, R
Abstract : Background: Pain is a common symptom in polyneuropathies (PNPs), although it is still not known why some PNPs are painful and others are painless. Increased pro-inflammatory cytokines have been found in conditions resulting in exaggerated pain states in animal studies. Recently, elevated pro-inflammatory cytokine levels have also been found in the cerebrospinal fluid (CSF) of patients suffering from complex regional pain syndrome. Pro-inflammatory cytokines have been shown to induce or increase inflammatory or neuropathic pain. Methods: Using chemiluminescent enzyme immunometric assays, cytokine levels in 36 patients with painful and painless non-inflammatory PNPs in serum and CSF were investigated. The severity of PNPs was measured with electroneurography (ENG). In subjects with normal results using conventional ENG, quantitative thermo-testing was performed to investigate small-nerve-fibre function. Results: Interleukin (IL)-6 and tumour necrosis factor (TNF)-α in serum or CSF did not differ between patients with (n = 18) or without (n = 18) painful PNPs, whereas patients with mechanical allodynia (n = 5) had elevated serum TNF-α levels compared to those without allodynia. TNF-α and IL-6 serum levels were higher in patients with severe (n = 21) compared to those with mild neuropathy (n = 15), and showed a positive correlation with severity of neuropathy. Conclusions: Results suggest that nerve fibre degeneration and presence of mechanical allodynia in peripheral non-inflammatory neuropathy determine cytokine expression in serum.